Experiência como arte: John Dewey e a vanguarda artística estadunidense - Thiago Barros Gomes (2018)
This thesis is an investigation of the pragmatist philosophy of John Dewey's art and the assimilation of his aesthetic thinking by the American artistic avant-garde of the mid-twentieth century. It is argued that Dewey's concept of experience served for these vanguards to filter European artistic heritage and put art into a new key. Thus, Dewey's comprehensive concept of experience, his claim that art is an experience (an event), has created a new disposition in artists of Abstract Expressionism and Happening to abandon the notion of a work of art as a physical object restricted to a specific medium; and adopt a notion of a work of art in which art is experience and experience is art in the form of a participatory event